Can returning home for entrepreneurship improve the agricultural economic resilience: Investigation based on the pilot policy of returning home for entrepreneurship - Xiaowen Yu; Hongyu Ma (PLoS ONE, 2026)
Against the backdrop of the ongoing transition of rural China from a “labor migrant economy” to an “entrepreneurial economy”, this study utilizes panel data covering 2005 counties nationwide in China during the period 2012–2022. Employing a Difference-in-Differences (DID) model integrated with a mediating effect approach, this study comprehensively examines the impact of the pilot hometown-return entrepreneurship policy on agricultural economic resilience and its intrinsic mechanisms of action. The results show that agricultural economic resilience exhibits a steady upward trend and significant spatial disparity, characterized by a spatial distribution pattern of “high in the east, low in the west, high in the north, and low in the south”. The pilot hometown-return entrepreneurship policy exerts a significantly positive effect on enhancing agricultural economic resilience, with this positive impact being more pronounced in western China and less substantial in eastern China. Mechanism analysis reveals that increasing farmers’ income and advancing the rationalization of the industrial structure are the key transmission channels through which the pilot hometown-return entrepreneurship policy enhances agricultural economic resilience. These findings contribute to a better understanding of the extent to which and the mechanisms through which the pilot hometown-return entrepreneurship policy enhances agricultural economic resilience. It is imperative for all regions to continuously strengthen policy support and guidance for returning farmers and enhance regional attractiveness in light of local conditions, thereby fostering the high-quality development of the agricultural economy.